Mobile agents : basic concepts, mobility models, and the Tracy toolkit - Braun, Peter, Dr.; Rossak, Wilhelm (San Francisco, CA : Elsevier : Morgan Kaufmann ; Heidelberg : Dpunkt.verlag, 2005)
Mobile agents are software nomads that act as your personal representative, working autonomously through networks. They are able to visit network nodes directly using available computing power and are not limited by platform. This emerging field is now poised to become a cornerstone for new Web-based ubiquitous computing environments. Mobile Agents provides a practical introduction to mobile agent technology and surveys the state of the art in mobile agent research. Students and researchers can use the book as an introduction to the concepts and possibilities of this field and as an overview of ongoing research. Developers can use it to identify the capabilities of the technology to decide if mobile agents are the right solution for them. Practioners can also gain hands-on experience in programming mobile agents through exploration of the source code for a complete mobile agent environment available through the companion website. *Summarizes the state of the art in mobile agent research *Identifies the benefits and limitations of current mobile agent technology to help developers understand the possibilities of this new field *Extensive mobile agents web portal (www.mobile-agents.org) with the Java source code for a complete industrial-quality environment for mobile agents, with significant parts of the system open source.
Designing innovative distributed systems -- From client-server to mobile agents -- Mobile agent migration -- Mobile agent communication -- Mobile agent security -- Specifications of the Kalong mobility model -- Using Kalong -- Evaluation -- Running a Tracy agency -- Programming agents with Tracy.
Διαθέσιμο και σε ηλεκτρονικό βιβλίο, τρόπος πρόσβασης μέσω διαδικτύου.
Includes bibliographical references (p. 401-418) and index.
Keywords: Mobile agents (Computer software).; Agents mobiles (Logiciels); Electronic books